Genome Sequence of the Siphoviridae Staphylococcus aureus Phage vB_SauS_BaqSau1 (2020)
Here, we report the genome sequence of a Siphoviridae phage named vB_SauS_BaqSau1 (BaqSau1), infecting Staphylococcus aureus. Phage BaqSau1 was isolated from a sewage water treatment plant in Sahagún, Córdoba, Colombia. It has a double-stranded DNA (dsDNA) genome of 44,384 bp with 67 predicted genes, including a lysin containing a CHAP (cysteine, histidine-dependent amidohydrolase/ peptidase) domain.